Kinetic characterization of a membrane-specific ATPase from rat osseous plate and its possible significance on endochondral ossification - Pizauro, J. M.; Demenis, M. A.; Ciancaglini, P.; Leone, F. A. (Elsevier B.V., 1998)
Treatment with phosphatidylinositol-specific phospholipase C of rat osseous plate membranes released up to 90-95% of alkaline phosphatase, but a specific ATPase activity (optimum pH = 7.5) remained bound to the membrane. The hydrolysis of ATP by this ATPase was negligible in the absence of magnesium or calcium ions. However, at millimolar concentrations of magnesium and calcium ions, the membrane-specific ATPase activity increased to about 560-600 U/mg, exhibiting two classes of ATP-hydrolysing sites, and site-site interactions. GTP, UTP, ITP, and CTP were also hydrolyzed by the membrane-specific ATPase. Oligomycin, ouabain, bafilomycin A(1), thapsigargin, omeprazole, ethacrynic acid and EDTA slightly affected membrane-specific ATPase activity while vanadate produced a 18% inhibition. The membrane-specific ATPase activity was insensitive to theophylline, but was inhibited 40% by levamisole. These data suggested that the membrane-specific ATPase activity present in osseous plate membranes, and alkaline phosphatase, were different proteins. (C) 1998 Elsevier B.V. B.V.
Keywords: ATPase; Osseous plate; phosphatidylinositol-specific phospholipase C; endochondral ossification; Alkaline phosphatase